Książka jako przedmiot realizacji wartości kulturowych w Unii Europejskiej - Statkiewicz, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Books play a significant role in the preservation of cultural diversity within the European Union. Because of the binary character of the book as a cultural artifact, as well as an object of commerce, books are encompassed by special mechanisms of support and protection within the borders of the European Union. Their cultural value may also justify the unique treatment of books in the application of some of the provisions of the Treaties, e.g. in the areas of taxation, copyrights and competition law. Due to the EU legislation in the fields of VAT tax as well as copyrights, the Member States are able to highlight the valuable contribution of books concerning preservation, dissemination and development of national cultures. However, in the era of digital revolution, some of presented provisions are insufficient. Reduced rate of VAT tax cannot be applied to e-books, which were recognized by the Court of Justice of the European Union as electronically supplied services. Moreover, there is still lack of announced EU provisions on fixed book price. As a result, the Member States sharing the same language, are not able to establish joint fixed book price without breaking the European Union law.
Keywords: Unia Europejska; wartości kulturowe; książka